Meetings amongst Deaf and Hearing Students in the Mathematics Classroom - Moura, Amanda Queiroz [UNESP]; Penteado, Miriam Godoy [UNESP] (Open Book Publishers, 2022)
In this chapter, we are aiming to contribute to practices in mathematics classes that value the idea of meetings amongst differences. We present landscapes that were designed specifically in order to favour interaction among deaf and hearing students. The discussion is based on data produced in a public elementary school in Brazil, in a fifth-year class with both deaf and hearing students. The results highlight that the organisation of tasks based on dialogic communication is essential in order to respond to unpredictability and to enable collaboration in conditions of equity in the mathematics classroom.